Automated Fake Access Point Attack Detection and Prevention System with IoT Devices - Kilincer, İlhan Firat; Ertam, Fatih; Şengür, Abdülkadir (My University, 2020)
Wireless access points (APs), which allow many devices to be easily connected to the Internet, are widely used today because they offer the easiest way to connect to the Internet. With the development of the Internet of Things (IoT), WiFi networks are widely used in our homes, workplaces, social areas, campus areas. With the increase of WiFi networks, attacks on these networks are constantly increasing. In this study, an IoT-based approach to detect and prevent Fake Access point attacks frequently seen in WiFi networks is proposed. A Single Board Computer (SBC) and a wireless antenna in the \"Soft AP\" feature are used for operation. Fake APs were detected by air scanning. In the first phase of the study, fake Access point broadcasts have been created which can create security weakness. In order to determine the fake Access points created in the second stage, SBC and wifi module were used to scan air. In the final stage, the mac address of the fake AP has been assigned to an unauthorized Virtual Local Area Network (vLAN) on the network to prevent detected fake AP broadcasts. The possible attack methods for the study were implemented and it was revealed that the proposed approach prevented the attack successfully in all scenarios. The study is seen as an effective, developed and economically useful IoT application for network administrators to prevent the attack using fake Access point.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği